The mediating role of cognitive emotion regulation skills in the relationship between romantic relationship satisfaction and eating attitudes - Yilmazer, Eda; Turk, Fulya; Hamamci, Zeynep (SPRINGERNATURE, 2025)
Background Romantic relationship satisfaction has been linked to psychological outcomes, including emotional well-being and eating behaviors. However, the mechanisms underlying this relationship remain unclear. This study examines the mediating role of cognitive emotion regulation strategies-particularly catastrophizing-in the relationship between romantic relationship satisfaction and eating attitudes. Methods A cross-sectional study was conducted with 355 university students. Participants completed the Relationship Satisfaction Scale, the Cognitive Emotion Regulation Questionnaire (CERQ), and the Eating Attitudes Test-26 (EAT-26). Structural equation modeling (SEM) was performed using AMOS and R with robust maximum likelihood estimation. Model fit was evaluated using chi 2/df, CFI, GFI, RMSEA, and SRMR. Results Catastrophizing significantly mediated the relationship between romantic relationship satisfaction and eating attitudes. Romantic relationship satisfaction was negatively associated with catastrophizing (beta = -0.18, p = .028), and catastrophizing was positively associated with problematic eating attitudes (beta = 0.35, p < .001). The direct effect of romantic relationship satisfaction on eating attitudes was not statistically significant (beta = -0.12, p = .104), indicating full mediation. Acceptance did not significantly mediate the relationship (p = .348). Gender differences were observed: women scored significantly higher on rumination, dieting, and bulimia/food preoccupation (p < .05). Conclusions These findings highlight the role of maladaptive cognitive emotion regulation-specifically catastrophizing-in linking romantic relationship dissatisfaction with disordered eating attitudes. Targeting catastrophizing in interventions may improve both relationship satisfaction and eating behaviors.
Keywords: Cognitive emotion regulation; Romantic relationship Satisfaction; Eating attitudes; Maladaptive stratejies; Catastrophizing; REGULATION STRATEGIES; DEPRESSIVE SYMPTOMS; COPING STRATEGIES; SOCIAL SUPPORT; LIFE EVENTS; DISORDERS; PERSPECTIVE; PSYCHOPATHOLOGY; INTERDEPENDENCE; DYSREGULATION; Psychology